2001
DOI: 10.1002/1521-3749(200112)627:12<2647::aid-zaac2647>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Kantennahe Röntgenfeinstruktur-Untersuchungen an Oxidkeramiken von Chrom, Cobalt und Nickel in verschiedenen Oxidationsstufen und deren bindungschemische Interpretation

Abstract: Inhaltsu È bersicht. Es wird u È ber kantennahe Feinstruktur-Messungen (XANES) an Ûbergangsmetall-Oxidkeramiken berichtet und die Aussagekraft dieser Methode zur Bestimmung von Oxidationsstufen (Cobalt und Nickel (II bis IV), Chrom (III bis VI)) und der Bindungsverha È ltnisse diskutiert. Die Mischkristallreihe Nd 2±x Sr x NiO 4±d mit gemischtvalentem Nickel wird mit dieser Methode genauer charakterisiert und untersucht.Abstract. Results of X-ray absorption near edge structure (XANES) studies on selected trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…The transition from the low-spin one-peak spectrum to a broader spectrum is observed, but there is little peak shift and the spectral change is not very clear. Similar LaCoO 3 spectra have been measured [385,455], but as these data are obtained at room temperature they are a mixture between low-spin and high-spin. Simbock and coworkers studied the co-existence of low-spin and high-spin ions in LaCoO 3 systems of a series of catalytically active systems.…”
Section: Cobalt Oxidessupporting
confidence: 63%
See 3 more Smart Citations
“…The transition from the low-spin one-peak spectrum to a broader spectrum is observed, but there is little peak shift and the spectral change is not very clear. Similar LaCoO 3 spectra have been measured [385,455], but as these data are obtained at room temperature they are a mixture between low-spin and high-spin. Simbock and coworkers studied the co-existence of low-spin and high-spin ions in LaCoO 3 systems of a series of catalytically active systems.…”
Section: Cobalt Oxidessupporting
confidence: 63%
“…The low-spin (t 5 2g ) Co 4+ system SrCoO 3 shifts to lower energy with respect to low-spin Co 3+ oxides and a small shoulder is visible at low energy related to the empty t 2g state [455]. The (La,Sr)(Li,Co)O 3 system studied by Hu et al contains 40% Co 4+ and the spectral shape is a combination of the low-spin Co 3+ and Co 4+ peaks [449,455]. Harvey et al also measured the Co 4+ oxides SrCoO 3 and BaCoO 3 [451], but their observed spectral shapes look different, with significant Co 3+ contribution, in addition to large carbonate peaks that make the spectrum complex to analyse above 532 eV.…”
Section: Cobalt Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some weak pre-edge features (1s → 3d transition [10,11]) appearing as a shoulder of the main edge for all the nitridocobaltates at ∼7713 eV, are also observed. As expected, the Co K-edges of nitridocobaltates(I) are located at lower energy (shift ≈ 4 eV) in comparison with Co 3 O 4 which contains Co II/III .…”
Section: Discussionmentioning
confidence: 99%